The Rhotic Pronunciation of Anglo-English and Punjabi-English Bilingual Speakers in West Yorkshire (2017)
In this paper, the /r/ production of adolescent Anglo-English and Punjabi-English Bilingual speakers in West Yorkshire was analysed from speech data collected in 2000. A clear difference was found between Anglo-English speakers who used the standard British rhotic, the postalveolar approximant [ɹ̠], exclusively, and the Punjabi-English Bilingual speakers who used both British rhotics and a number of different variants influenced by the Punjabi retroflex flap /ɽ/. The influence of the retroflex flap /ɽ/ was proven by formant and duration results, as well as qualitative observations of the speaker spectrograms. It is predicted that Punjabi-English speaker preference for either Punjabi influenced rhotics or British rhotics depended on if they identify as culturally integrated “British Asians” or culturally alienated “Asians”. This study also considers the possibility of a progression in rhotic production of West Yorkshire Punjabi-English speakers over the last fifteen years.